PEMETAAN MIKROZONASI DAERAH RAWAN GEMPABUMI MENGGUNAKAN METODE HVSR DAERAH PAINAN SUMATERA BARAT - Asri Wulandari; Suharno Suharno; Rustadi Rustadi (Jurnal Geofisika Eksplorasi, 2018)
Regional Painan, the distric of Pesisir Selatan, the province of west Sumatera is one of the areas with high risk disaster prone. This study aims attempts to maped the disaster prone area of the Painan region based on the dominant frequency value, Vs30, PGA and amplification and to know the value of ground movement from the area. By using the HVSR method (Horizontal to Vertical Spectra Ratio) expected to assist to zone the regions. Based on the research that has been done, it is known that the Painan area, West Sumatera, have values of dominant frequency between 0.6 to 12.07 Hz. As for the value Vs30 between 73.08 to 1449 m/s and the amplification values between 0.47 to 6.01. The PGA value for Painan region between 0.034 to 0.063 g. Based on the analysis that has been done by correlating the four zoning map, it is known that the area which has a high risk of earthquake disaster that is estimated to coastal areas. This is supported by the dominant low frequency value and the value Vs30 small and PGA of high value. The amplification value of this region is divided into four zones, areas that have amplification is very high being around the beach and composed by rock alluvial, the value of amplification of high contained in nearly all the regions Painan while amplification medium and low are the small area of Painan and the small area of Bungo Pasang Salido because based on the geological map of the area is composed of two types of rocks are alluvial and rock Painan Formations.